Differentiation of ecological niche patterns between sympatric lemurs in northwestern Madagascar: Implications for their conservation - Fernando Mercado Malabet; Finaritra T. Randimbiarison; Jean Claude Razafimampiandra; Bertrand Andriatsitohaina; Coral Chell; Mamy Razafitsalama; Travis S. Steffens; Shawn M. Lehman (PLoS ONE, 2026)
Understanding how species respond to habitat loss and fragmentation is a critical requirement for effective conservation action, particularly in biodiversity hotspots like Madagascar. Species with specialized, narrower ecological niche requirements are hypothesized to be more vulnerable to extinction than generalists, yet empirical tests of this prediction among closely related taxa remain limited. Here, we compare the ecological niche patterns and predicted distributions of two sympatric lemurs in northwestern Madagascar – the Vulnerable Common Brown Lemur ( Eulemur fulvus ) and the Critically Endangered Mongoose Lemur ( Eulemur mongoz ) – to assess how niche flexibility relates to extinction risk. Using presence-only data collected between 2015 and 2020 and ten environmental covariates, we developed species distribution models and ran niche equivalence analysis. The models indicate that E. fulvus occupies a broader and more continuous predicted distribution range (48,591 ha) than E. mongoz (17,757 ha). In comparison, E. mongoz is predicted to occur primarily in moist lowland forests near water basins, showing a stronger spatial association with these habitat conditions that E. fulvus . Despite these marked differences in their predicted geographic distributions, niche equivalence analysis showed substantial overlap in the environmental conditions occupied by the two species within the study area. Together, these results suggest that E. mongoz’s restricted distribution is not explained solely by the measured environmental predictors, highlighting the need for future work that integrates additional environmental variables and evaluates potential behavioural or demographic constraints not captured here. These findings highlight how subtle differences in niche requirements can shape a species’ habitat use and vulnerability to environmental change. From a management perspective, our findings support prioritizing the protection of moist lowland forests near water basins for E. mongoz while maintaining or enhancing habitat connectivity for E. fulvus in fragmented landscapes.